2012
DOI: 10.3897/compcytogen.v6i2.2595
|View full text |Cite
|
Sign up to set email alerts
|

First karyotype description of Hypostomus iheringii (Regan, 1908): a case of heterochromatic polymorphism

Abstract: In this study, which is the first karyotype analysis of Hypostomus iheringii, nine specimens collected in Córrego da Lapa (tributary of the Passa-Cinco River) showed a diploid number of 80 chromosomes. Silver nitrate staining and fluorescence in situ hybridization (FISH) with an 18S rDNA probe revealed the presence of multiple nucleolus organizer regions (NORs) (chromosome pairs 13, 20, and 34). FISH with a 5S rDNA probe showed that this cistron was only present in chromosome pair 2. When the karyotypes of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
(60 reference statements)
1
24
0
Order By: Relevance
“…This condition, that we found for the 18S rDNA site of chromosome pair 15 in H. ancistroides, was previously observed in H. regani (Mendes-Neto et al, 2011) and H. iheringii (Traldi et al, 2012). Possibly, it is due to the limited sensitivity of the technique for detecting very small sites (Schwarzacher and Heslop-Harrison, 2000).…”
Section: Physical Mapping Of Ribosomal Genes In Hypostomussupporting
confidence: 51%
See 2 more Smart Citations
“…This condition, that we found for the 18S rDNA site of chromosome pair 15 in H. ancistroides, was previously observed in H. regani (Mendes-Neto et al, 2011) and H. iheringii (Traldi et al, 2012). Possibly, it is due to the limited sensitivity of the technique for detecting very small sites (Schwarzacher and Heslop-Harrison, 2000).…”
Section: Physical Mapping Of Ribosomal Genes In Hypostomussupporting
confidence: 51%
“…FISH confirmed the variation of the 18S rDNA sites noticed in species of Hypostomus and made possible the identification of the numerical and positional diversity of rDNA 5S sites (Kavalco et al, 2004;Mendes-Neto et al, 2011;Rubert et al, 2011;Traldi et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Some studies have suggested that the heterochromatin in CP regions might suppress or silence gene expression by the reversible transformation between heterochromatin and euchromatin [17,18]. In addition, other reports have indicated that the heterochromatin located at centromeres plays an essential role in cell division.…”
Section: Discussionmentioning
confidence: 99%
“…In Hypostomus, data on the physical location of 5S rDNA sites are still scarce, but variations in the number and position of these markings have been reported (Traldi et al, 2012). H. iheringii was found to have only one pair of chromosomes marked by FISH 5S (Traldi et al, 2012), H. regani had nine sites identified (Mendes-Neto et al, 2011), and H. affinis (Kavalco et al, 2005) and H. cf.…”
Section: Discussionmentioning
confidence: 99%